Preparation method of high-strength antibacterial acrylic material

By preparing antibacterial nanocellulose and modifying and combining with glycyrrhizic acid, grafting PMMA, the cross-infection and insufficient antibacterial performance of existing acrylic materials in high flow places are solved, and acrylic materials with high strength and significant antibacterial properties are achieved.

CN119859368AActive Publication Date: 2025-04-22东莞丽佳塑胶有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510178093.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-18
Publication Date
2025-04-22
Estimated Expiration
2045-02-18

AI Technical Summary

Technical Problem

Existing acrylic materials are prone to cross infection in places with large flow of people, and poor compatibility of antibacterial agents leads to uneven distribution, affecting product quality. At the same time, the strength and impact resistance of the material are insufficient.

Method used

By preparing antibacterial nanocellulose and modifying it with glycyrrhizic acid, grafting PMMA to form a high-strength antibacterial acrylic material. The method includes preparing a cupric ammonia solution using copper hydroxide and ammonia water, adding cellulose and thiourea for dissolution and sonication, followed by electrospinning, and finally obtaining a high-strength antibacterial acrylic material by hot pressing.

Benefits of technology

The high mechanical strength, durability and significant antibacterial properties of acrylic materials are achieved, ensuring the safety and durability of the materials in high traffic places.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859368A_ABST
    Figure CN119859368A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, in particular to a preparation method of a high-strength antibacterial acrylic material. Comprising the following steps: preparing antibacterial nanocellulose; modifying antibacterial nano cellulose by glycyrrhizic acid; and preparing the antibacterial cellulose-PMMA and polymethyl methacrylate compound. The antibacterial cellulose-PMMA is prepared by taking antibacterial nano cellulose as a matrix, reacting a hydroxyl group with alpha-dibromopropionyl bromide and then initiating polymerization of methyl methacrylate, and the antibacterial cellulose-PMMA has good mechanical strength and rigidity due to a macromolecular structure of cellulose, so that the antibacterial cellulose-PMMA has a good antibacterial property. In addition, by adding PMMA, the acrylic material has good compatibility with the acrylic material, when the acrylic material is subjected to blending polymerization with methyl methacrylate, nanoscale cellulose can be uniformly distributed in an acrylic matrix, and in conclusion, the mechanical property and the antibacterial property of the acrylic material can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to a method for preparing a high-strength antibacterial acrylic material. Background Art

[0002] Acrylic, also known as polymethyl methacrylate (PMMA), is an important transparent polymer material widely used in construction, advertising, transportation, medicine, lighting and other fields. Acrylic has many excellent properties, including high light transmittance, high toughness, high resistance to fragmentation, etc., which leads to the increasing demand for acrylic materials in various fields.

[0003] Acrylic materials are often used in the preparation of display screens, covers of sports equipment, isolation fences, and bathroom toilets. These products are often placed in places with large traffic, such as gyms, stadiums, and public toilets. These places are easily touched by people and cause cross infection. In order to avoid this situation, the antibacterial property of acrylic materials is particularly important. The existing methods of giving acrylic materials antibacterial ability are almost all to add antibacterial agents during the preparation process. These antibacterial agents are mainly inorganic powders such as nanosilver and silver-loaded composite materials. They have poor compatibility with polymethyl methacrylate and are easy to move and aggregate in polymethyl methacrylate, resulting in uneven distribution, affecting product quality. In addition, in order to make acrylic materials more durable in these places with large traffic, the strength and impact resistance of acrylic materials are also crucial. Summary of the invention

[0004] In order to solve the above technical defects, the present invention has developed a method for preparing a high-strength antibacterial acrylic material. The prepared acrylic material not only has excellent antibacterial properties, but also has high mechanical strength and strong durability.

[0005] A method for preparing a high-strength antibacterial acrylic material comprises the following steps: S1: Preparation of antibacterial nanocellulose The copper hydroxide and ammonia water are mixed, thiourea and cellulose pulp are added, and the mixture is stirred to obtain a copper ammonia cellulose solution, a polyethylene oxide aqueous solution is prepared, and the mixture is mixed with the copper ammonia cellulose solution for ultrasonic treatment, and then electrostatic spinning is performed, and the obtained cellulose film layer is scraped off, collected, and dried to obtain antibacterial nanocellulose; S2: Glycyrrhizic acid modified antibacterial nanocellulose The ion exchange resin and tetrabutylammonium hydroxide are mixed and stirred, and then filtered and washed to obtain tetrabutylammonium modified resin; disodium glycyrrhizinate is dissolved in deionized water, and the tetrabutylammonium modified resin is added, stirred, and then filtered and freeze-dried to obtain tetrabutylammonium modified glycyrrhizic acid; tetrabutylammonium modified glycyrrhizic acid is dissolved in N, N-dimethylformamide, 1-ethyl-(3-dimethylaminopropyl) carbodiimide and N-hydroxysuccinimide are added, stirred, and then an antibacterial nanocellulose solution prepared by mixing antibacterial nanocellulose and N, N-dimethylformamide is added, sealed and shaken, and after the temperature reaction, the reaction solution is dialyzed with deionized water, centrifuged and freeze-dried to obtain glycyrrhizic acid modified nanocellulose; S3: Preparation of antibacterial cellulose-PMMA and polymethyl methacrylate composites The glycyrrhizic acid-modified nanocellulose is dissolved in N, N-dimethylformamide, and α-dibromopropionyl bromide is added. After stirring and washing, the mixture is centrifuged to obtain brominated nanocellulose. Under a nitrogen atmosphere, the brominated nanocellulose, methyl methacrylate and pentamethyldipropylenetriamine are dissolved in N, N-dimethylformamide, and CuBr is added to seal the reaction. The mixture is then taken out and deionized water is added for centrifugal separation. The supernatant is collected and freeze-dried to obtain antibacterial cellulose-PMMA. Methyl methacrylate and dibenzoyl peroxide are prepolymerized by heating and stirring. Antibacterial cellulose-PMMA, a comonomer, a cross-linking agent, zinc stearate and dioctyl phosphate are added. The mixture is heated and stirred to polymerize. The mixture is then degassed and hot-pressed to obtain a high-strength antibacterial acrylic material.

[0006] Furthermore, the preparation of antibacterial nanocellulose in step S1 comprises the following steps: S1.1: 4-6 parts by mass of copper hydroxide are placed in a container, 80-100 parts by mass of ammonia water are added, and then magnetic stirring is performed at a stirring speed of 200-250 rpm for 10-15 minutes to obtain a copper ammonia solution, and then 2-3 parts by mass of thiourea and 6-8 parts by mass of cellulose pulp are added, and magnetic stirring is continued at a stirring speed of 300-400 rpm for 20-25 minutes to obtain a copper ammonia cellulose solution; S1.2: Mix 2-3 parts by mass of polyethylene oxide and 95-100 parts by mass of deionized water in a container, stir until the polyethylene oxide is completely dissolved to obtain a polyethylene oxide aqueous solution, mix the cuprammonium cellulose solution obtained in step S1.1 and the polyethylene oxide aqueous solution in a mass ratio of 1:(1-2), then place in an ultrasonic disperser, adjust the ultrasonic frequency to 25-30 kHz, and perform ultrasonic treatment for 8-10 minutes to obtain an antibacterial cellulose spinning solution; S1.3: Place the antibacterial cellulose spinning solution in the syringe of the electrospinning machine, adjust the distance between the syringe needle and the receiving plate to 1.5-2cm, and the relative humidity of the environment to 40-60%. Then start the electrospinning machine, and perform electrospinning at a voltage of 15-20kV and a syringe pushing speed of 15-20μL / min. Then scrape and collect the cellulose film layer formed on the receiving plate, and place it in an oven at 60-65℃ to dry for 2-2.5 hours to obtain antibacterial nanocellulose.

[0007] Furthermore, step S2 of glycyrrhizic acid-modified antibacterial nanocellulose comprises the following steps: S2.1: placing an ion exchange resin and 1.2-1.5 mol / L tetrabutylammonium hydroxide in a container at a solid-liquid ratio of 1:(1.8-2), stirring for 3-3.5 hours, filtering, and washing the filtered solid with deionized water for 3-4 times to obtain a tetrabutylammonium modified resin, placing 1-1.5 parts by mass of disodium glycyrrhizinate in a container, adding 80-100 parts by mass of deionized water, stirring until the disodium glycyrrhizinate is completely dissolved, and then adding 35-40 parts by mass of tetrabutylammonium modified resin, stirring for 10-12 hours, filtering, and obtaining a filtrate, placing the filtrate in a freeze dryer for freeze drying, and obtaining tetrabutylammonium modified glycyrrhizic acid; S2.2: 0.4-0.6 parts by weight of antibacterial nanocellulose and 15-20 parts by weight of N, N-dimethylformamide are mixed in a container, and magnetic stirring is performed at a stirring speed of 450-500 rpm for 10-20 minutes to obtain an antibacterial nanocellulose solution. Under a nitrogen atmosphere, 0.2-0.3 parts by weight of tetrabutylammonium-modified glycyrrhizic acid and 12-15 parts by weight of N, N-dimethylformamide are mixed in a container, and stirred until the tetrabutylammonium-modified glycyrrhizic acid is completely dissolved, and then 0.4-0.5 parts by weight of 1-ethyl- (3-dimethylaminopropyl) carbodiimide and 0.3-0.32 parts by mass of N-hydroxysuccinimide are stirred for 30-35 minutes, then the antibacterial nanocellulose solution is added, the mixture is sealed and oscillated up and down for 6-8 minutes, then heated to 40-45°C and kept warm for 20-24 hours to obtain a reaction solution, the reaction solution is placed in a dialysis bag and dialyzed against deionized water for 45-50 hours, then placed in a centrifuge and centrifuged at a speed of 4000-4500 rpm for 3-4 minutes, the supernatant is separated and collected, and freeze-dried to obtain glycyrrhizic acid-modified nanocellulose.

[0008] Furthermore, step S3 prepares the antibacterial cellulose-PMMA and polymethyl methacrylate composite, comprising the following steps: S3.1: 0.6-0.8 parts by weight of glycyrrhizic acid-modified nanocellulose and 25-30 parts by weight of N,N-dimethylformamide are mixed and magnetically stirred for 15-20 minutes, and then 0.1-0.2 parts by weight of α-dibromopropionyl bromide are added, and stirring is continued for 20-24 hours, and then poured into 120-150 parts by weight of deionized water for washing, and the supernatant is collected by centrifugation, and freeze-dried to obtain brominated nanocellulose; S3.2: Add 0.6-0.8 parts by weight of brominated nanocellulose, 2-2.5 parts by weight of methyl methacrylate and 0.4-0.5 parts by weight of pentamethyldipropylenetriamine into a container, then add 50-60 parts by weight of N,N-dimethylformamide under a nitrogen atmosphere and stir until the solid is completely dissolved, then add 0.4-0.45 parts by weight of CuBr and seal the container, heat to 60-65°C and evacuate to vacuum, maintain the vacuum for 25-30 minutes, then introduce nitrogen to restore the air pressure in the container to one atmosphere, keep warm for 22-24 hours, then take out and add 1-2 times the volume of deionized water, centrifuge to collect the supernatant, and freeze-dry to obtain antibacterial cellulose-PMMA; S3.3: Mix 90-100 parts by mass of methyl methacrylate and 0.3-0.5 parts by mass of dibenzoyl peroxide, stir at 50-60°C at a stirring speed of 150-200rpm for 10-15 minutes, then add 8-10 parts by mass of antibacterial cellulose-PMMA, 15-20 parts by mass of comonomer, 2-4 parts by mass of cross-linking agent, 1-3 parts by mass of zinc stearate and 1-1.5 parts by mass of dioctyl phosphate, heat to 80-85°C, continue to stir at a stirring speed of 120-150rpm for 1-1.5 hours, perform vacuum degassing after cooling, and then inject into a tempered glass mold for hot pressing molding. The hot pressing temperature is 120-150°C, the hot pressing pressure is 40-60Kpa, and the heat and pressure are maintained for 2-3 hours to obtain a high-strength antibacterial acrylic material.

[0009] Furthermore, the mass fraction of the aqueous ammonia in step S1.1 is 20-25%.

[0010] Furthermore, in step S1.1, the degree of polymerization of the cellulose pulp is 1000-1100, and the α-cellulose content of the cellulose pulp is 90-95%.

[0011] Furthermore, the ion exchange resin in step S2.1 is a strongly acidic cation exchange resin Amberlyst15.

[0012] Furthermore, the dialysis bag cutoff in step S2.2 is 1-1.2 kDa.

[0013] Furthermore, the comonomer in step S3.3 consists of methacrylamide and allyl methacrylate in a molar ratio of 1:(1-2).

[0014] Furthermore, the cross-linking agent in step S3.3 is butanediol dipropylene glycol.

[0015] The beneficial effects are as follows: 1. The present invention prepares a copper ammonia solution by mixing copper hydroxide and ammonia water, then dissolves cellulose pulp to obtain a copper ammonia cellulose solution, and then prepares a polyethylene oxide aqueous solution and a copper ammonia cellulose solution, mixes them by ultrasound, and performs electrostatic spinning. In this process, copper ions with excellent antibacterial properties can coordinate with hydroxyl groups to obtain antibacterial nanocellulose. Subsequently, the antibacterial nanocellulose is used as a matrix, and α-dibromopropionyl bromide is reacted through hydroxyl groups, and then methyl methacrylate is polymerized by atom transfer radical polymerization to obtain antibacterial cellulose-PMMA. Since cellulose has a polymer structure, it itself has good mechanical strength and rigidity. By connecting PMMA, it can also have good compatibility with acrylic materials. When co-polymerized with methyl methacrylate, nano-scale cellulose can be evenly distributed in the acrylic matrix. In summary, the mechanical properties and antibacterial properties of the acrylic material can be significantly improved.

[0016] 2. The present invention firstly performs lipophilic modification on glycyrrhizic acid by tetrabutylammonium hydroxide so that it can be better dissolved in N, N-dimethylformamide and can fully carry out subsequent reactions. Then, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide are added for mediation, and glycyrrhizic acid is introduced into the antibacterial nanocellulose through a carboxylamino coupling reaction. Glycyrrhizic acid has the ability to scavenge oxygen free radicals and inhibit bacterial metabolism, which can not only provide antioxidant capacity for the antibacterial nanocellulose, but also reduce the oxidation of free radicals in the system during subsequent polymerization with MMA, improve the stability of polymerization, improve the mechanical properties of acrylic materials, and further enhance the antibacterial properties of acrylic materials.

[0017] 3. The present invention adds thiourea during the process of dissolving cellulose pulp in a copper ammonia solution, which not only ensures that cellulose is not oxidized and degraded, but also thiourea can react with NH3 in ammonia water to form thiosemicarbazide, and thiosemicarbazide can form a complex with copper ions to enhance the antibacterial activity of copper ions. The formed complex can better adhere to cellulose, further enhancing the antibacterial properties and antibacterial stability of acrylic materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a flow chart of the preparation method of the high-strength antibacterial acrylic material used in an embodiment of the present invention. DETAILED DESCRIPTION

[0019] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0020] A method for preparing a high-strength antibacterial acrylic material, such as Figure 1 As shown, the following steps are included: S1: Preparation of antibacterial nanocellulose S1.1: 4 parts by mass of copper hydroxide are placed in a container, 80 parts by mass of 20% ammonia water are added, and then magnetic stirring is performed at a stirring speed of 200 rpm for 10 minutes to obtain a copper ammonia solution, and then 2 parts by mass of thiourea and 6 parts by mass of cellulose pulp are added, the degree of polymerization of the cellulose pulp is 1000, and the α-cellulose content is 90%, and magnetic stirring is continued at a stirring speed of 300 rpm for 20 minutes to obtain a copper ammonia cellulose solution; S1.2: Mix 2 parts by mass of polyethylene oxide and 95 parts by mass of deionized water in a container and stir until the polyethylene oxide is completely dissolved to obtain a polyethylene oxide aqueous solution. Mix the cuprammonium cellulose solution obtained in step S1.1 and the polyethylene oxide aqueous solution in a mass ratio of 1:1, and then place in an ultrasonic disperser, adjust the ultrasonic frequency to 25 kHz, and perform ultrasonic treatment for 8 minutes to obtain an antibacterial cellulose spinning solution; S1.3: Place the antibacterial cellulose spinning solution in the syringe of the electrospinning machine, adjust the distance between the syringe needle and the receiving plate to 1.5 cm, and the relative humidity of the environment to 40%. Then start the electrospinning machine, and perform electrospinning at a voltage of 15 kV and a syringe pushing speed of 15 μL / min. Then, scrape and collect the cellulose film layer formed on the receiving plate, and place it in an oven at 60°C to dry for 2 hours to obtain antibacterial nanocellulose.

[0021] S2: Glycyrrhizic acid modified antibacterial nanocellulose S2.1: A strong acidic cation exchange resin Amberlyst15 and 1.2 mol / L tetrabutylammonium hydroxide are placed in a container at a solid-liquid ratio of 1:1.8, and the mixture is stirred for 3 hours and then filtered. The solid obtained by filtration is rinsed with deionized water for 3 times to obtain a tetrabutylammonium modified resin. 1 part by mass of disodium glycyrrhizinate is placed in a container, 80 parts by mass of deionized water are added, and the mixture is stirred until the disodium glycyrrhizinate is completely dissolved. Then, 35 parts by mass of tetrabutylammonium modified resin are added, and the mixture is stirred for 10 hours and then filtered to obtain a filtrate. The filtrate is placed in a freeze dryer for freeze drying to obtain tetrabutylammonium modified glycyrrhizic acid; S2.2: 0.4 parts by mass of antibacterial nanocellulose and 15 parts by mass of N, N-dimethylformamide were mixed in a container and magnetically stirred at a stirring speed of 450 rpm for 10 minutes to obtain an antibacterial nanocellulose solution. Under a nitrogen atmosphere, 0.2 parts by mass of tetrabutylammonium-modified glycyrrhizic acid and 12 parts by mass of N, N-dimethylformamide were mixed in a container and stirred until the tetrabutylammonium-modified glycyrrhizic acid was completely dissolved. Then, 0.4 parts by mass of 1-ethyl-(3-dimethylformamide) was added. 2-(4-(2-methylaminopropyl)carbodiimide and 0.3 parts by mass of N-hydroxysuccinimide, stirring for 30 minutes, then adding the antibacterial nanocellulose solution, sealing and oscillating up and down for 6 minutes, then heating to 40°C and keeping warm for 20 hours to obtain a reaction solution, the reaction solution was placed in a dialysis bag with a cutoff of 1 kDa and dialyzed against deionized water for 45 hours, then placed in a centrifuge and centrifuged at 4000 rpm for 3 minutes, the supernatant was separated and collected, and freeze-dried to obtain glycyrrhizic acid-modified nanocellulose.

[0022] S3: Preparation of antibacterial cellulose-PMMA and polymethyl methacrylate composites S3.1: 0.6 parts by mass of glycyrrhizic acid-modified nanocellulose and 25 parts by mass of N,N-dimethylformamide were mixed and magnetically stirred for 15 minutes, and then 0.1 parts by mass of α-dibromopropionyl bromide was added, and stirring was continued for 20 hours, and then poured into 120 parts by mass of deionized water for washing, and the supernatant was collected by centrifugation and freeze-dried to obtain brominated nanocellulose; S3.2: Add 0.6 parts by mass of brominated nanocellulose, 2 parts by mass of methyl methacrylate and 0.4 parts by mass of pentamethyldipropylenetriamine into a container, then add 50 parts by mass of N,N-dimethylformamide under a nitrogen atmosphere and stir until the solid is completely dissolved, then add 0.4 parts by mass of CuBr and seal the container, heat to 60°C and evacuate to vacuum, maintain the vacuum for 25 minutes and then introduce nitrogen to restore the air pressure in the container to one atmosphere, keep warm for 22 hours, then take out and add 1 volume of deionized water, centrifuge to collect the supernatant, and freeze-dry to obtain antibacterial cellulose-PMMA; S3.3: Mix 90 parts by mass of methyl methacrylate and 0.3 parts by mass of dibenzoyl peroxide, stir at 50°C at a stirring speed of 150 rpm for 10 minutes, then add 8 parts by mass of antibacterial cellulose-PMMA, 15 parts by mass of a copolymer monomer consisting of methacrylamide and allyl methacrylate in a molar ratio of 1:1, 2 parts by mass of butanediol dipropylene glycol, 1 part by mass of zinc stearate and 1 part by mass of dioctyl phosphate, heat to 80°C, continue stirring at a stirring speed of 120 rpm for 1 hour, perform vacuum degassing after cooling, and then inject into a tempered glass mold for hot pressing molding. The hot pressing temperature is 120°C and the hot pressing pressure is 40 Kpa. Keep warm and press for 2 hours to obtain a high-strength antibacterial acrylic material. Example 2

[0023] A method for preparing a high-strength antibacterial acrylic material, such as Figure 1 As shown, the following steps are included: S1: Preparation of antibacterial nanocellulose S1.1: 6 parts by mass of copper hydroxide are placed in a container, 100 parts by mass of 20% ammonia water are added, and then magnetic stirring is performed at a stirring speed of 200 rpm for 10 minutes to obtain a copper ammonia solution, and then 3 parts by mass of thiourea and 8 parts by mass of cellulose pulp are added, the degree of polymerization of the cellulose pulp is 1000, and the α-cellulose content is 90%, and magnetic stirring is continued at a stirring speed of 300 rpm for 20 minutes to obtain a copper ammonia cellulose solution; S1.2: Mix 3 parts by mass of polyethylene oxide and 100 parts by mass of deionized water in a container, stir until the polyethylene oxide is completely dissolved to obtain a polyethylene oxide aqueous solution, mix the cuprammonium cellulose solution obtained in step S1.1 and the polyethylene oxide aqueous solution in a mass ratio of 1:2, and then place in an ultrasonic disperser, adjust the ultrasonic frequency to 25 kHz, and perform ultrasonic treatment for 8 minutes to obtain an antibacterial cellulose spinning solution; S1.3: Place the antibacterial cellulose spinning solution in the syringe of the electrospinning machine, adjust the distance between the syringe needle and the receiving plate to 1.5 cm, and the relative humidity of the environment to 40%. Then start the electrospinning machine, and perform electrospinning at a voltage of 15 kV and a syringe pushing speed of 15 μL / min. Then, scrape and collect the cellulose film layer formed on the receiving plate, and place it in an oven at 60°C to dry for 2 hours to obtain antibacterial nanocellulose.

[0024] S2: Glycyrrhizic acid modified antibacterial nanocellulose S2.1: A strong acidic cation exchange resin Amberlyst15 and 1.2 mol / L tetrabutylammonium hydroxide are placed in a container at a solid-liquid ratio of 1:2, and the mixture is stirred for 3 hours and then filtered. The solid obtained by filtration is rinsed with deionized water for 3 times to obtain a tetrabutylammonium modified resin. 1.5 parts by mass of disodium glycyrrhizinate are placed in a container, 100 parts by mass of deionized water are added, and the mixture is stirred until the disodium glycyrrhizinate is completely dissolved. Then, 40 parts by mass of tetrabutylammonium modified resin are added, and the mixture is stirred for 10 hours and then filtered to obtain a filtrate. The filtrate is placed in a freeze dryer for freeze drying to obtain tetrabutylammonium modified glycyrrhizic acid. S2.2: 0.6 parts by mass of antibacterial nanocellulose and 20 parts by mass of N, N-dimethylformamide were mixed in a container and magnetically stirred at a stirring speed of 450 rpm for 10 minutes to obtain an antibacterial nanocellulose solution. Under a nitrogen atmosphere, 0.3 parts by mass of tetrabutylammonium-modified glycyrrhizic acid and 15 parts by mass of N, N-dimethylformamide were mixed in a container and stirred until the tetrabutylammonium-modified glycyrrhizic acid was completely dissolved. Then, 0.5 parts by mass of 1-ethyl-(3-dimethylformamide) was added. The mixture was stirred for 30 minutes, and then the antibacterial nanocellulose solution was added. The mixture was sealed and oscillated up and down for 6 minutes, and then heated to 40°C and kept warm for 20 hours to obtain a reaction solution. The reaction solution was placed in a dialysis bag with a cutoff of 1 kDa and dialyzed against deionized water for 45 hours. The solution was then placed in a centrifuge and centrifuged at 4000 rpm for 3 minutes. The supernatant was separated and collected, and then freeze-dried to obtain glycyrrhizic acid-modified nanocellulose.

[0025] S3: Preparation of antibacterial cellulose-PMMA and polymethyl methacrylate composites S3.1: 0.6 parts by mass of glycyrrhizic acid-modified nanocellulose and 25 parts by mass of N,N-dimethylformamide were mixed and magnetically stirred for 15 minutes, and then 0.1 parts by mass of α-dibromopropionyl bromide was added, and stirring was continued for 20 hours, and then poured into 120 parts by mass of deionized water for washing, and the supernatant was collected by centrifugation and freeze-dried to obtain brominated nanocellulose; S3.2: 0.8 parts by mass of brominated nanocellulose, 2.5 parts by mass of methyl methacrylate and 0.5 parts by mass of pentamethyldipropylenetriamine were added to a container, and then 60 parts by mass of N,N-dimethylformamide were added under a nitrogen atmosphere and stirred until the solid was completely dissolved, and then 0.45 parts by mass of CuBr were added and the container was sealed, and the mixture was heated to 60°C and evacuated to a vacuum, and nitrogen was introduced after maintaining the vacuum for 25 minutes to restore the air pressure in the container to one atmosphere, and the mixture was kept warm for 22 hours, and then 1 volume of deionized water was added, and the supernatant was collected by centrifugation and freeze-dried to obtain antibacterial cellulose-PMMA; S3.3: Mix 100 parts by mass of methyl methacrylate and 0.5 parts by mass of dibenzoyl peroxide, stir at 50°C at a stirring speed of 150 rpm for 10 minutes, then add 10 parts by mass of antibacterial cellulose-PMMA, 20 parts by mass of a copolymer monomer consisting of methacrylamide and allyl methacrylate in a molar ratio of 1:2, 4 parts by mass of butanediol dipropylene glycol, 3 parts by mass of zinc stearate and 1.5 parts by mass of dioctyl phosphate, raise the temperature to 80°C, continue stirring at a stirring speed of 120 rpm for 1 hour, perform vacuum degassing after cooling, and then inject into a tempered glass mold for hot pressing molding. The hot pressing temperature is 120°C and the hot pressing pressure is 40 Kpa. Keep warm and press for 2 hours to obtain a high-strength antibacterial acrylic material. Example 3

[0026] A method for preparing a high-strength antibacterial acrylic material, such as Figure 1 As shown, the following steps are included: S1: Preparation of antibacterial nanocellulose S1.1: 4 parts by mass of copper hydroxide are placed in a container, 80 parts by mass of 25% ammonia water are added, and then magnetic stirring is performed at a stirring speed of 250 rpm for 15 minutes to obtain a copper ammonia solution, and then 2 parts by mass of thiourea and 6 parts by mass of cellulose pulp are added, the degree of polymerization of the cellulose pulp is 1100, and the α-cellulose content is 95%, and magnetic stirring is continued at a stirring speed of 400 rpm for 25 minutes to obtain a copper ammonia cellulose solution; S1.2: Mix 2 parts by mass of polyethylene oxide and 95 parts by mass of deionized water in a container and stir until the polyethylene oxide is completely dissolved to obtain a polyethylene oxide aqueous solution. Mix the cuprammonium cellulose solution obtained in step S1.1 and the polyethylene oxide aqueous solution in a mass ratio of 1:1, and then place in an ultrasonic disperser, adjust the ultrasonic frequency to 30 kHz, and perform ultrasonic treatment for 10 minutes to obtain an antibacterial cellulose spinning solution; S1.3: Place the antibacterial cellulose spinning solution in the syringe of the electrospinning machine, adjust the distance between the syringe needle and the receiving plate to 2 cm, and the relative humidity of the environment to 60%. Then start the electrospinning machine, and perform electrospinning at a voltage of 20 kV and a syringe pushing speed of 20 μL / min. Then, scrape and collect the cellulose film layer formed on the receiving plate, and place it in an oven at 65°C to dry for 2.5 hours to obtain antibacterial nanocellulose.

[0027] S2: Glycyrrhizic acid modified antibacterial nanocellulose S2.1: A strong acidic cation exchange resin Amberlyst15 and 1.5 mol / L tetrabutylammonium hydroxide are placed in a container at a solid-liquid ratio of 1:1.8, and the mixture is stirred for 3.5 hours and then filtered. The solid obtained by filtration is rinsed with deionized water 4 times to obtain a tetrabutylammonium modified resin. 1 part by mass of disodium glycyrrhizinate is placed in a container, 80 parts by mass of deionized water are added, and the mixture is stirred until the disodium glycyrrhizinate is completely dissolved. Then, 35 parts by mass of tetrabutylammonium modified resin are added, and the mixture is stirred for 12 hours and then filtered to obtain a filtrate. The filtrate is placed in a freeze dryer for freeze drying to obtain tetrabutylammonium modified glycyrrhizic acid; S2.2: 0.4 parts by mass of antibacterial nanocellulose and 15 parts by mass of N, N-dimethylformamide were mixed in a container and magnetically stirred at a stirring speed of 500 rpm for 20 minutes to obtain an antibacterial nanocellulose solution. Under a nitrogen atmosphere, 0.2 parts by mass of tetrabutylammonium-modified glycyrrhizic acid and 12 parts by mass of N, N-dimethylformamide were mixed in a container and stirred until the tetrabutylammonium-modified glycyrrhizic acid was completely dissolved. Then, 0.4 parts by mass of 1-ethyl-(3-dimethylformamide) was added. The mixture was stirred for 35 minutes, and then the antibacterial nanocellulose solution was added. The mixture was sealed and oscillated up and down for 8 minutes, and then heated to 45°C and kept warm for 24 hours to obtain a reaction solution. The reaction solution was placed in a dialysis bag with a cutoff of 1.2 kDa and dialyzed against deionized water for 50 hours. The solution was then placed in a centrifuge and centrifuged at 4500 rpm for 4 minutes. The supernatant was separated and collected, and then freeze-dried to obtain glycyrrhizic acid-modified nanocellulose.

[0028] S3: Preparation of antibacterial cellulose-PMMA and polymethyl methacrylate composites S3.1: 0.6 parts by mass of glycyrrhizic acid-modified nanocellulose and 25 parts by mass of N,N-dimethylformamide were mixed and magnetically stirred for 20 minutes, and then 0.1 parts by mass of α-dibromopropionyl bromide was added, and stirring was continued for 24 hours, and then poured into 120 parts by mass of deionized water for washing, and the supernatant was collected by centrifugation and freeze-dried to obtain brominated nanocellulose; S3.2: Add 0.6 parts by mass of brominated nanocellulose, 2 parts by mass of methyl methacrylate and 0.4 parts by mass of pentamethyldipropylenetriamine into a container, then add 50 parts by mass of N,N-dimethylformamide under a nitrogen atmosphere and stir until the solid is completely dissolved, then add 0.4 parts by mass of CuBr and seal the container, heat to 65°C and evacuate to vacuum, maintain the vacuum for 30 minutes and then introduce nitrogen to restore the air pressure in the container to one atmosphere, keep warm for 24 hours, then take out and add 2 times the volume of deionized water, centrifuge to collect the supernatant, and freeze-dry to obtain antibacterial cellulose-PMMA; S3.3: Mix 90 parts by mass of methyl methacrylate and 0.3 parts by mass of dibenzoyl peroxide, stir at 60°C at a stirring speed of 200 rpm for 15 minutes, then add 8 parts by mass of antibacterial cellulose-PMMA, 15 parts by mass of a copolymer monomer consisting of methacrylamide and allyl methacrylate in a molar ratio of 1:1, 2 parts by mass of butanediol dipropylene glycol, 1 part by mass of zinc stearate and 1 part by mass of dioctyl phosphate, heat to 85°C, continue stirring at a stirring speed of 150 rpm for 1.5 hours, perform vacuum degassing after cooling, and then inject into a tempered glass mold for hot pressing molding. The hot pressing temperature is 150°C and the hot pressing pressure is 60 Kpa. Keep warm and press for 3 hours to obtain a high-strength antibacterial acrylic material.

[0029] Comparative Example 1 Compared with Example 1, the difference of Comparative Example 1 is that Comparative Example 1 removes step S3.1 and step S3.2, replaces the antibacterial cellulose-PMMA in step S3.3 with glycyrrhizic acid-modified nanocellulose of equal mass, and the remaining steps are the same as those in Example 1. The obtained high-strength antibacterial acrylic material is recorded as Comparative Example 1.

[0030] Comparative Example 2 Compared with Example 1, the difference of Comparative Example 2 is that step S2 is removed in Comparative Example 2, and the glycyrrhizic acid-modified nanocellulose in step S3.1 is replaced with antibacterial nanocellulose of equal mass, and the remaining steps are the same as those in Example 1. The obtained high-strength antibacterial acrylic material is recorded as Comparative Example 2.

[0031] Comparative Example 3 Compared with Example 1, the difference of Comparative Example 3 is that, in Comparative Example 3, the thiourea in step S.1 is replaced with an equal mass of sodium sulfite, and the remaining steps are the same as those in Example 1. The obtained high-strength antibacterial acrylic material is recorded as Comparative Example 3.

[0032] Experiment 1: Take the high-strength antibacterial acrylic materials prepared in Examples 1-3 and Comparative Examples 1-2 as samples, test their tensile strength on a universal testing machine according to GB / T1040-92 standard, and test their impact strength on a pendulum impact tester according to GB / T1843-1996 standard. Take 8 samples for each embodiment and comparative example, and take the average value of the test as the test result, as shown in Table 1.

[0033] Table 1: Mechanical properties of high-strength antibacterial acrylic materials

[0034] It can be seen from the data of Examples 1-3 and Comparative Examples 1-2 in Table 1 that the tensile strength and impact strength of the examples are higher than those of Comparative Examples 1-2, which can prove that using antibacterial nanocellulose as a matrix, reacting with α-dibromopropionyl bromide through hydroxyl groups, and then initiating polymerization of methyl methacrylate through atom transfer radical polymerization, and accessing PMMA on glycyrrhizic acid-modified nanocellulose can improve the compatibility of glycyrrhizic acid-modified nanocellulose with acrylic materials, making it evenly distributed in the acrylic matrix, thereby improving the mechanical properties of the acrylic material; It can also be proved that the modification of antibacterial nanocellulose with glycyrrhizic acid can provide antioxidant capacity for antibacterial nanocellulose, reduce the oxidation of free radicals in the system during subsequent polymerization with MMA, improve the stability of polymerization, and improve the mechanical properties of acrylic materials.

[0035] Experiment 2: The high-strength antibacterial acrylic materials prepared in Examples 1-3 and Comparative Examples 1-3 were taken as samples, and their surfaces were sterilized by ultraviolet light for 30 minutes. Then, 100 μL of Escherichia coli suspension (10 8 CFU / mL) and 100 μL of Staphylococcus aureus suspension (1×10 8 CFU / mL), the plate count method was used to determine the number of viable bacteria in 100μL Escherichia coli suspension and 100μL Staphylococcus aureus suspension, recorded as N0, and then the solution was applied to the sample surface with an area of ​​1cm×1cm. The solution was incubated for 1 hour at a relative humidity of not less than 90% and 37℃ light. The bacterial solution on the sample surface was then resuspended with sterile saline, and the number of viable bacteria was determined by the plate count method, recorded as N1. The inhibition rate n% was calculated as (N0-N1) / N0×100%. The higher the inhibition rate, the better the antibacterial performance. Three parallel experiments were performed on each sample, and the inhibition rate was averaged, as shown in Table 2.

[0036] Table 2: Antibacterial rate of high-strength antibacterial acrylic materials

[0037] It can be seen from the data of the embodiment and comparative example 1 in Table 2 that the glycyrrhizic acid-modified nanocellulose was not brominated, and then the antibacterial cellulose-PMMA was prepared by obtaining brominated nanocellulose grafted PMMA. The antibacterial property of the acrylic material decreased. It can be proved that the preparation of antibacterial cellulose-PMMA helps to disperse cellulose in the acrylic matrix and improve its antibacterial property.

[0038] It can be seen from the data of Example 2 and Comparative Example 2 that the antibacterial nanocellulose is not modified with glycyrrhizic acid, and the antibacterial property of the acrylic material is significantly reduced. It can be proved that the antibacterial nanocellulose modified with glycyrrhizic acid can improve the antibacterial property of the acrylic material through the inhibitory ability of glycyrrhizic acid on bacterial metabolism.

[0039] It can be seen from the data of Example 2 and Comparative Example 3 that after thiourea in the process of dissolving cellulose in the copper ammonia solution is replaced by sodium sulfite, the antibacterial property of the acrylic material decreases. It can be proved that the addition of thiourea can improve the antibacterial activity of copper ions and further enhance the antibacterial property of the acrylic material.

[0040] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for preparing a high-strength antibacterial acrylic material, characterized in that: The following steps are involved: S1: Preparation of antibacterial nanocellulose The copper hydroxide and ammonia water are mixed, thiourea and cellulose pulp are added, and the mixture is stirred to obtain a copper ammonia cellulose solution, a polyethylene oxide aqueous solution is prepared, and the mixture is mixed with the copper ammonia cellulose solution for ultrasonic treatment, and then electrostatic spinning is performed, and the obtained cellulose film layer is scraped off, collected, and dried to obtain antibacterial nanocellulose; S2: Glycyrrhizic acid modified antibacterial nanocellulose The ion exchange resin and tetrabutylammonium hydroxide are mixed and stirred, and then filtered and washed to obtain tetrabutylammonium modified resin; disodium glycyrrhizinate is dissolved in deionized water, and the tetrabutylammonium modified resin is added, stirred, and then filtered and freeze-dried to obtain tetrabutylammonium modified glycyrrhizic acid; tetrabutylammonium modified glycyrrhizic acid is dissolved in N, N-dimethylformamide, 1-ethyl-(3-dimethylaminopropyl) carbodiimide and N-hydroxysuccinimide are added, stirred, and then an antibacterial nanocellulose solution prepared by mixing antibacterial nanocellulose and N, N-dimethylformamide is added, sealed and shaken, and after the temperature reaction, the reaction solution is dialyzed with deionized water, centrifuged and freeze-dried to obtain glycyrrhizic acid modified nanocellulose; S3: Preparation of antibacterial cellulose-PMMA and polymethyl methacrylate composites The glycyrrhizic acid-modified nanocellulose is dissolved in N, N-dimethylformamide, and α-dibromopropionyl bromide is added. After stirring and washing, the mixture is centrifuged to obtain brominated nanocellulose. Under a nitrogen atmosphere, the brominated nanocellulose, methyl methacrylate and pentamethyldipropylenetriamine are dissolved in N, N-dimethylformamide, and CuBr is added to seal the reaction. The mixture is then taken out and deionized water is added for centrifugal separation. The supernatant is collected and freeze-dried to obtain antibacterial cellulose-PMMA. Methyl methacrylate and dibenzoyl peroxide are prepolymerized by heating and stirring. Antibacterial cellulose-PMMA, a comonomer, a cross-linking agent, zinc stearate and dioctyl phosphate are added. The mixture is heated and stirred to polymerize. The mixture is then degassed and hot-pressed to obtain a high-strength antibacterial acrylic material.

2. The method for preparing a high-strength antibacterial acrylic material according to claim 1, characterized in that: Step S1: Preparation of antibacterial nanocellulose, comprising the following steps: S1.1: 4-6 parts by mass of copper hydroxide are placed in a container, 80-100 parts by mass of ammonia water are added, and then magnetic stirring is performed at a stirring speed of 200-250 rpm for 10-15 minutes to obtain a copper ammonia solution, and then 2-3 parts by mass of thiourea and 6-8 parts by mass of cellulose pulp are added, and magnetic stirring is continued at a stirring speed of 300-400 rpm for 20-25 minutes to obtain a copper ammonia cellulose solution; S1.2: Mix 2-3 parts by mass of polyethylene oxide and 95-100 parts by mass of deionized water in a container, stir until the polyethylene oxide is completely dissolved to obtain a polyethylene oxide aqueous solution, mix the cuprammonium cellulose solution obtained in step S1.1 and the polyethylene oxide aqueous solution in a mass ratio of 1:(1-2), then place in an ultrasonic disperser, adjust the ultrasonic frequency to 25-30 kHz, and perform ultrasonic treatment for 8-10 minutes to obtain an antibacterial cellulose spinning solution; S1.3: Place the antibacterial cellulose spinning solution in the syringe of the electrospinning machine, adjust the distance between the syringe needle and the receiving plate to 1.5-2cm, and the relative humidity of the environment to 40-60%. Then start the electrospinning machine, and perform electrospinning at a voltage of 15-20kV and a syringe pushing speed of 15-20μL / min. Then scrape and collect the cellulose film layer formed on the receiving plate, and place it in an oven at 60-65℃ to dry for 2-2.5 hours to obtain antibacterial nanocellulose.

3. The method for preparing a high-strength antibacterial acrylic material according to claim 2, characterized in that: Step S2: glycyrrhizic acid-modified antibacterial nanocellulose, comprising the following steps: S2.1: placing an ion exchange resin and 1.2-1.5 mol / L tetrabutylammonium hydroxide in a container at a solid-liquid ratio of 1:(1.8-2), stirring for 3-3.5 hours, filtering, and washing the filtered solid with deionized water for 3-4 times to obtain a tetrabutylammonium modified resin, placing 1-1.5 parts by mass of disodium glycyrrhizinate in a container, adding 80-100 parts by mass of deionized water, stirring until the disodium glycyrrhizinate is completely dissolved, and then adding 35-40 parts by mass of tetrabutylammonium modified resin, stirring for 10-12 hours, filtering, and obtaining a filtrate, placing the filtrate in a freeze dryer for freeze drying, and obtaining tetrabutylammonium modified glycyrrhizic acid; S2.2: 0.4-0.6 parts by weight of antibacterial nanocellulose and 15-20 parts by weight of N, N-dimethylformamide are mixed in a container, and magnetic stirring is performed at a stirring speed of 450-500 rpm for 10-20 minutes to obtain an antibacterial nanocellulose solution. Under a nitrogen atmosphere, 0.2-0.3 parts by weight of tetrabutylammonium-modified glycyrrhizic acid and 12-15 parts by weight of N, N-dimethylformamide are mixed in a container, and stirred until the tetrabutylammonium-modified glycyrrhizic acid is completely dissolved, and then 0.4-0.5 parts by weight of 1-ethyl- (3-dimethylaminopropyl) carbodiimide and 0.3-0.32 parts by mass of N-hydroxysuccinimide are stirred for 30-35 minutes, then the antibacterial nanocellulose solution is added, the mixture is sealed and oscillated up and down for 6-8 minutes, then heated to 40-45°C and kept warm for 20-24 hours to obtain a reaction solution, the reaction solution is placed in a dialysis bag and dialyzed against deionized water for 45-50 hours, then placed in a centrifuge and centrifuged at a speed of 4000-4500 rpm for 3-4 minutes, the supernatant is separated and collected, and freeze-dried to obtain glycyrrhizic acid-modified nanocellulose.

4. The method for preparing a high-strength antibacterial acrylic material according to claim 3, characterized in that: Step S3 prepares the antibacterial cellulose-PMMA and polymethyl methacrylate composite, comprising the following steps: S3.1: 0.6-0.8 parts by weight of glycyrrhizic acid-modified nanocellulose and 25-30 parts by weight of N,N-dimethylformamide are mixed and magnetically stirred for 15-20 minutes, and then 0.1-0.2 parts by weight of α-dibromopropionyl bromide are added, and stirring is continued for 20-24 hours, and then poured into 120-150 parts by weight of deionized water for washing, and the supernatant is collected by centrifugation, and freeze-dried to obtain brominated nanocellulose; S3.2: Add 0.6-0.8 parts by weight of brominated nanocellulose, 2-2.5 parts by weight of methyl methacrylate and 0.4-0.5 parts by weight of pentamethyldipropylenetriamine into a container, then add 50-60 parts by weight of N,N-dimethylformamide under a nitrogen atmosphere and stir until the solid is completely dissolved, then add 0.4-0.45 parts by weight of CuBr and seal the container, heat to 60-65°C and evacuate to vacuum, maintain the vacuum for 25-30 minutes, then introduce nitrogen to restore the air pressure in the container to one atmosphere, keep warm for 22-24 hours, then take out and add 1-2 times the volume of deionized water, centrifuge to collect the supernatant, and freeze-dry to obtain antibacterial cellulose-PMMA; S3.3: Mix 90-100 parts by mass of methyl methacrylate and 0.3-0.5 parts by mass of dibenzoyl peroxide, stir at 50-60°C at a stirring speed of 150-200rpm for 10-15 minutes, then add 8-10 parts by mass of antibacterial cellulose-PMMA, 15-20 parts by mass of comonomer, 2-4 parts by mass of cross-linking agent, 1-3 parts by mass of zinc stearate and 1-1.5 parts by mass of dioctyl phosphate, heat to 80-85°C, continue to stir at a stirring speed of 120-150rpm for 1-1.5 hours, perform vacuum degassing after cooling, and then inject into a tempered glass mold for hot pressing molding. The hot pressing temperature is 120-150°C, the hot pressing pressure is 40-60Kpa, and the heat and pressure are maintained for 2-3 hours to obtain a high-strength antibacterial acrylic material.

5. The method for preparing a high-strength antibacterial acrylic material according to claim 2, characterized in that: The mass fraction of aqueous ammonia in step S1.1 is 20-25%.

6. The method for preparing a high-strength antibacterial acrylic material according to claim 2, characterized in that: The degree of polymerization of the cellulose pulp in step S1.1 is 1000-1100, and the α-cellulose content of the cellulose pulp is 90-95%.

7. The method for preparing a high-strength antibacterial acrylic material according to claim 3, characterized in that: The ion exchange resin in step S2.1 is the strongly acidic cation exchange resin Amberlyst15.

8. The method for preparing a high-strength antibacterial acrylic material according to claim 3, characterized in that: The dialysis bag cutoff in step S2.2 is 1-1.2 kDa.

9. The method for preparing a high-strength antibacterial acrylic material according to claim 4, characterized in that: The comonomers in step S3.3 consist of methacrylamide and allyl methacrylate in a molar ratio of 1:(1-2).

10. The method for preparing a high-strength antibacterial acrylic material according to claim 4, characterized in that: The cross-linking agent in step S3.3 is butanediol dipropylene glycol.

Citation Information

Patent Citations

  • High-voltage static atomizing preparing technique for nano-grade cellulosic material

    CN101139805A

  • Degradable medical injector material and preparation method thereof

    CN109135151A

  • Cellulose dispersion liquid composition, production method thereof and cellulosic resin composite material

    JP2020111638A

  • Cellulose dispersion composition and cellulose resin composite material

    JP2022051784A

  • Modified nano-cellulose and method for producing same, and resin composition containing modified nano-cellulose

    WO2013133436A1